PENGAWASAN PEMERINTAH KOTA PEKANBARU TERHADAP PELARANGAN PEMASANGAN REKLAME ROKOK DI KAWASAN TANPA ROKOK (KTR) TAHUN 2019 – 2020 - Tryandani, Nefy; Harirah, Zulfa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
No-smoking areas are a way to reduce health-harming tobacco smoke pollution, tobacco smoke can cause lung cancer, heart disease, asthma in children, and sudden infant death. Non-smoking areas include health service facilities, teaching and learning places and other places as regulated in Pekanbaru Mayor Regulation No. 39/2014 on No Smoking Areas. One of the prohibitions is the installation of cigarette billboards in the No-Smoking Area of Pekanbaru City. However, the supervision is still weak since the Mayor Regulation was implemented until 2019-2020. The local government is still cheating on cigarette billboards in the no-smoking area. Lack of firm sanctions, and a lack of compliance by employers with the Perwako. The formulation of the problem of this research is: "How is Pekanbaru City Government Supervision of the Ban on the Installation of Cigarette Cigarette Billboards in Non-Smoking Areas in 2019-2020?" This study aims to analyze and describe the supervision of the Pekanbaru City government against the prohibition of installing cigarette billboards in smoke-free areas in 2019-2020. This research is a descriptive research using a qualitative approach. Data collection techniques in this study using interview techniques, observation and documentation, data analysis used is qualitative analysis. The findings can be concluded that Pekanbaru City Government's Supervision of the Prohibition of Cigarette Billboards in the No-Smoking Area of Pekanbaru City is still classified as weak, even though 1) The government has a standard of supervision in accordance with the Regulation of the Mayor of Pekanbaru No. 39/2014 on No Smoking Areas. 2) the supervisory measurement system is to monitor every working day (Monday-Friday) in the administrative area of Pekanbaru City and coordinate with other agencies; 3) However, in the measurement, the implementation of the supervision is still not optimal so that there are cigarette billboards displayed in the KTR area; 4) as for the analysis of the causes of deviation from the supervisory standards, namely lack of human resources, less than optimal personnel performance, low level of entrepreneur compliance, lack of coordination between government agencies, local government political interests and weak application of sanctions; 5) corrective action taken by the government in the form of intensive future supervision, additional human resources and budget, increasing intergovernmental coordination and imposing strict sanctions.Keywords: Standard Setting, Measurement Determination, Implementation Measurement, Comparative Implementation, and Corrective Action Taking